Corydalis kangxianensis (Papaveraceae), a new species from the western Qinling Mountains, southern Gansu, China - Wang, Dong; Xu, Xiaodong; Chen, Yu; Dai, Quanhua; Wang, Liang (Phytotaxa, 2025)
Corydalis kangxianensis (Papaveraceae), a new species from Kangxian county in southern Gansu, China, is described and illustrated. This new species clearly belongs to Corydalis sect. Incisae sensu Zhang et al. (2008). It is similar to C. pseudoamplisepala D.Wang, but differs in the outer petals being broadly rounded (vs. ovate) and obtuse to emarginate (vs. subacute) at apex, having much smaller sepals (0.8–1.4 × 0.6–0.8 vs. 1.5–2.0 × 1.0–1.5 mm), and capsules that are narrowly to broadly obovoid (vs. broadly obovoid). It is also similar to C. amplisepala Z.Y.Su & Lidén and C. austroshaanxiensis D.Wang, but it is readily distinguishable from both by its outer petals without crest (vs. with crest). Molecular phylogenetic analysis further supports its recognition as a distinct species. An identification key to C. kangxianensis and related species is provided. This study underscores the need for further botanical surveys in remote and less-explored mountainous regions to better document the species diversity of Corydalis.